An Executive’s Guide for Moving From U.S. GAAP to IFRS - Walton, Peter (Business Expert, 2012)
The book reviews different issues relating to the possibility that the Securities and Exchange Commission (SEC) may eventually mandate the use of International Financial Reporting Standards (IFRS) for use by listed companies and delegate to the International Accounting Standards Board (IASB) the task of providing accounting standards for the United States. The fi rst chapter reviews the international movement to converge on a single global basis of accounting for listed companies. It also discusses the experience of European companies, where 25 countries adopted IFRS in 2005. The second chapter analyzes the position in the United States. It looks at the advantages and disadvantages for corporations and explains the convergence program being followed by the Financial Accounting Standards Board (FASB) and the IASB. It also looks at the SEC’s activities in this area and then sets out the challenges to be addressed by U.S. corporations if IFRS are adopted. Canada has made the decision to switch in 2011, and the Canadian experience is discussed as offering a blueprint for the United States. This is followed by an extensive analysis of the technical differences between IFRS and U.S. Generally Accepted Accounting Principles (GAAP). The last two chapters explain the organizational structure of the IASB and its standard-setting process, and then the evolution of the international standard-setter from its beginning in 1973.